2010
DOI: 10.1007/978-1-60761-711-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Specific Biomarkers in Renal Medicine and Research

Abstract: Histopathology is the gold standard for defining renal injury, but it is invasive, time-consuming and expensive, plus it is seldom used in subjects with mild renal injury. Using biomarkers linked to distinct, defined cell types and tissues provides a direct link to histopathology without its drawbacks, plus it provides increased sensitivity, and specificity. The nephron consists of several sections, each with its own specific biomarkers; therefore, by the use of a battery of tests injuries can be localised to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 114 publications
2
2
0
Order By: Relevance
“…role in CP-induced damage, and several antioxidants and thiol compounds have been reported to mitigate or protect against CP nephrotoxicity [8,29]. Here, we have confirmed that CP depletes renal GSH and other enzymes involved in scavenging of free radicals, and that pretreatment and concomitant treatment with emodin significantly reverses these changes.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…role in CP-induced damage, and several antioxidants and thiol compounds have been reported to mitigate or protect against CP nephrotoxicity [8,29]. Here, we have confirmed that CP depletes renal GSH and other enzymes involved in scavenging of free radicals, and that pretreatment and concomitant treatment with emodin significantly reverses these changes.…”
Section: Discussionsupporting
confidence: 79%
“…GSH has been shown in several in vivo and in vitro studies to protect against CP nephrotoxicity, and CP is metabolized to a nephrotoxicant through a GSH‐conjugate intermediate [36]. Oxidative stress has been reported to play a role in CP‐induced damage, and several antioxidants and thiol compounds have been reported to mitigate or protect against CP nephrotoxicity [8,29]. Here, we have confirmed that CP depletes renal GSH and other enzymes involved in scavenging of free radicals, and that pretreatment and concomitant treatment with emodin significantly reverses these changes.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations